Digital Libraries: Providing Quality Information : 17th International Conference on Asia-Pacific Digital Libraries, ICADL 2015, Seoul, Korea, December 9-12, 2015. Proceedings - Allen, Robert B.; Hunter, Jane.; Zeng, Marcia L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 17th International Conference on Asia-Pacific Digital Libraries, ICADL 2015, held in Seoul, South Korea, in December 2015. The 22 full papers, 9 short papers, 7 panels, 6 doctoral consortiium papers and 19 poster papers presented were carefully reviewed and selected from 141 submissions. The papers for this 2015 conference cover topics such as digital preservation, gamification, text mining, citizen science, data citation, linked data, and cloud computing.
Digital preservation -- Gamication -- Text mining -- Citizen science -- Data citation -- Linked data -- Cloud computing. .
Keywords: Information storage and retrieva; Natural language processing (Computer science).; Database management; Artificial intelligence; Computer Communication Networks; Information Storage and Retrieval; Natural Language Processing (NLP).; Database Management; Information Systems Applications (incl. Internet).; Artificial Intelligence; Computer Communication Networks